2011
DOI: 10.1080/03630242.2011.560999
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women's Fear of Childbirth in Midwife- and Obstetrician-Led Care in Belgium and the Netherlands: Test of the Medicalization Hypothesis

Abstract: Fear of childbirth has gained importance in the context of increasing medicalization of childbirth.Belgian and the Dutch societies are very similar but differ with regard to the organization of maternity care. The Dutch have a high percentage of home births and low medical intervention rates.In contrast, home births in Belgium are rarer, and the medical model is more widely used. By comparing the Belgian and the Dutch maternity care models we explored the association between fear of childbirth and medicalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…During the postpartum period, the most prominent areas causing fear and a dire need for information among mothers included: postpartum care and complications (Christiaens et al 2011); infant nutrition and care (Christie et al 2008;Karata ş 2001); postpartum exercises; adaptation to parenthood and family planning (Y ı ld ı z 2008). In Kitap ç ı o ğ lu et al (2008), the three most prominent fears among pregnant women were regarding the behaviour of healthcare personnel during childbirth (7.2); fear about infant health (7.0); and fear about childbirth itself (6.92).…”
Section: Discussionmentioning
confidence: 99%
“…During the postpartum period, the most prominent areas causing fear and a dire need for information among mothers included: postpartum care and complications (Christiaens et al 2011); infant nutrition and care (Christie et al 2008;Karata ş 2001); postpartum exercises; adaptation to parenthood and family planning (Y ı ld ı z 2008). In Kitap ç ı o ğ lu et al (2008), the three most prominent fears among pregnant women were regarding the behaviour of healthcare personnel during childbirth (7.2); fear about infant health (7.0); and fear about childbirth itself (6.92).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the other participating countries, almost all Belgian women receive all their antenatal care from one obstetrician who also supervises their subsequent birth at the hospital (9). Thus, Belgium has highly medicalized care and exceptional continuity of carer (9). None of the other countries achieves the same level of continuity of carer, except for a minority of women participating in special midwifery-led care models (12,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Denmark were more likely to meet a known midwife in labour (12). The second study explored the association between FOC and medicalization by comparing 833 Belgian and Dutch pregnant women's attitudes towards childbirth using a four-dimensional model based on the W-DEQ (9). This study concluded that Belgian women in midwifery care were more fearful of medical interventions and hospital care compared to Dutch women receiving midwifery care.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations